Uncertainty and the real economy: Evidence from Denmark - Mikkel Bess; Erik Grenestam; Alessandro Tang-Andersen Martinello; Jesper Pedersen (Danmarks Nationalbank, 2020)
We construct an index for economic policy uncertainty in Denmark using articles in Denmark's largest financial newspaper. We adapt a Latent Dirichlet Allocation (LDA) model to sort articles into topics. We combine article-specific topic weights with the occurrence of words describing uncertainty to construct our index. We then incorporate the index in a structural VAR model of the Danish economy and find that uncertainty is a robust predictor of investments and employment. According to our model, increased uncertainty contributed significantly to the drop in investments during the Sovereign Debt Crisis. Conversely, uncertainty has so far had a smaller, but still significant, impact on investments during the COVID-19 pandemic.
Keywords: D80; E66; 330; Economic activity and employment; Current economic and monetary trends; Statistical method